Поширення грибів роду Costantinella Matr. в Україні - Гавриш, Поліна Вікторівна; Акулов, Олександр Юрійович; Havrysh, P.V. (My University, 2020)
Information about two Costantinella species – C. micheneri and C. terrestris, collected by A. Pilát from the territory of Carpathian Biosphere Reserve (Zakarpattia region), and by us from National Nature Park «Hetmanskyi» (Sumy region) are represented.
Distribution of the fungi which are Costantinella Matr. representatives in Ukraine.
Keywords: гриби; біорізноманіття; Costantinella; Morchella